PENGEMBANGAN E-MODUL INTERAKTIF PADA MATERI PELUANG SISWA KELAS VIII SMP NEGERI 1 TILONGKABILA - Olvi Muliyani Kudji; Evi P. Hulukati; Dewi Rahmawaty Isa (PHI: Jurnal Pendidikan Matematika, 2026)
This study aims to develop an interactive e-module on probability material for eighth-grade students of SMP Negeri 1 Tilongkabila. This research employed a Research and Development (R&D) method using the Plomp model, which includes preliminary investigation, design, product development, testing and revision, and limited implementation. The research subjects consisted of two material experts, one media expert, one mathematics teacher, and eighth-grade students. Data were collected through expert validation sheets and teacher and student response questionnaires, and analyzed using descriptive quantitative techniques.The results showed that the interactive e-module was categorized as very valid by material experts with a percentage of 98%, and valid by media experts with 81.54%. Teacher and student responses reached 89.17% and 87.78%, respectively, indicating very positive responses. Therefore, the interactive e-module on probability material is valid, practical, and suitable for use in mathematics learning for eighth-grade junior high school students..